Hemodynamic and hormonal actions of adrenomedullin - Nicholls,M.G. (2004)
Adrenomedullin, a 52-amino acid residue peptide, has numerous biological actions which are of potential importance to cardiovascular homeostasis, growth and development of cardiovascular tissues and bone, prevention of infection, and regulation of body fluid and electrolyte balance. Studies in man using intravenous infusion of the peptide have demonstrated that, at plasma levels detected after myocardial infarction or in heart failure, adrenomedullin reduces arterial pressure, increases heart rate and cardiac output, and activates the sympathetic and renin-angiotensin systems but suppresses aldosterone. The thresholds for these responses differ, being lower under some experimental circumstances for arterial pressure than for the other biological effects. Adrenomedullin administration inhibits the pressor and aldosterone-stimulating action of angiotensin II in man. By contrast, the pressor effect of norepinephrine is little altered by concomitant adrenomedullin administration. Although in the absence of a safe, specific antagonist of the actions of endogenous adrenomedullin it is difficult to be certain about the physiological and pathophysiological importance of this peptide in man, current evidence suggests that it serves to protect against cardiovascular overload and injury. Hope has been expressed that adrenomedullin or an agonist specific for adrenomedullin receptors might find a place in the treatment of cardiovascular disorders.